A new combination in Asian Clinopodium (Lamiaceae) - Turner, Ian (Phytotaxa, 2014)
Clinopodium umbrosum (M.Bieb.) Koch (1849: 673) was originally described from Georgia. A broad view of this species, which ranges from the Mediterranean to East Asia, has been maintained by some authors employing this name (Cramer 1981, Leblebici 1982, Clement 1999) or one of its homotypic synonyms (e.g. Satureja umbrosa (M.Beib.) Scheele (1843: 577), Keng 1978). However, from the Himalayas eastward one or more different species have been recognised by others. The name C. repens (D.Don) Benth. in Wallich (1830: 66) has been used for the eastern element in two major Chinese floras (Wu & Hsuan 1977, Li & Hedge 1994), although it was not noted that this name was first validly used for a South American species, published by Vellozo in 1829 (Stafleu & Cowan 1988), the year before Bentham transferred Thymus repens Don (1825: 113) to Clinopodium. Clinopodium repens (D.Don) Benth. in Wallich (1830: 66) is therefore an illegitimate later homonym and cannot be used. The next available synonym appears to be Ziziphora javanica Blume (1826: 822), described from Java. As there is no combination in Clinopodium for this basionym, I propose a new combination below: